1968
DOI: 10.1111/j.1151-2916.1968.tb15952.x
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Thermal Evolution of Amorphous Hvdrated Zirconium Oxide

Abstract: The thermal behavior of amorphous hydrated zirconium oxide and its coprecipitates with other oxides was studied.Solid solution with a limit of solubility seems to exist in the amorphous coprecipitates. A relation with the hightemperature solid solution was established. The structure of the amorphous zirconia was studied by X-ray and neutron diffraction; a thin plate model related to the structure of tetragonal zirconia is proposed. Heating the precipitates in an oxygen-free atmosphere produced a black nonstoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
2
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(116 citation statements)
references
References 11 publications
6
107
2
1
Order By: Relevance
“…Sorrentino et al [29] studied a number of other oxides and concluded that coalescence of particles is responsible for the glow. On the other hand Keshavaraja et al [27] and Livage et al [40] associate the glow exotherm with crystallization. In summary, the literature does not clearly identify the reaction providing the heat for the glow.…”
Section: Events During Thermal Treatmentmentioning
confidence: 99%
“…Sorrentino et al [29] studied a number of other oxides and concluded that coalescence of particles is responsible for the glow. On the other hand Keshavaraja et al [27] and Livage et al [40] associate the glow exotherm with crystallization. In summary, the literature does not clearly identify the reaction providing the heat for the glow.…”
Section: Events During Thermal Treatmentmentioning
confidence: 99%
“…The stabilization of t-ZrO 2 at low temperatures are governed by several factors such as the crystallite size effect, 1,2,18,19 the existence of stabilizers (variety and amount), 20,21 the presence of anionic impurities, 18,19 the domain boundaries, 22 and structural similarities between the tetragonal phase and the amorphous phase of the precursor. 19,23,24 In comparison with pure ZrO 2 , the metastability of the tetragonal phase for the doped zirconia can be observed in a wider range of temperatures due to the presence of oxygen vacancies. 5,6 Previously, various explanations have been proposed for the observed metastability of t-ZrO 2 .…”
Section: +mentioning
confidence: 99%
“…Theunissen (21) used a high temperature Guinier camera for XRD (heating rate 15°C/hr) and observed the first appearance of diffraction lines of the tetragonal phase at 400°C. Livage et al (22) found from a series of isothermal experiments that the minimum temperature required for complete crystallization of pure ZrO 2 in air equals 350°C. It can thus be concluded, that temperatures of 350 -400°C are needed for complete crystallization of zirconia in air.…”
Section: Microstructures After Sinterin~ At 1050°cmentioning
confidence: 99%